THE IMPACT OF LOCUS OF CONTROL AND OCCUPATIONAL STRESS ON EMPLOYEE PERFORMANCE AT PT BANK BCA TBK AREA MANADO - Siwy, Dominic Emanuela Chinara; Mangantar, Maryam; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2025)
This study investigates the Impact of locus of control and occupational stress on employee performance at PT Bank BCA Tbk Area Manado. The research adopts a quantitative approach, utilizing surveys to collect data from employees. The results show that both locus of control (X1) (with an emphasis on internal vs. external orientation) and occupational stress (X2) significantly impact employee performance (Y). Employees with a strong internal locus of control exhibit higher performance, while increased levels of stress are associated with lower performance. This study emphasizes the importance of creating a work environment that minimizes stress and encourages a sense of control to enhance employee performance at PT Bank BCA Tbk Area Manado. Keywords: Locus Of Control, Occupational Stress, Employee Performance